Lignin content as an estimator of rumen degradability of grasses (Semiárida, 2020)
The objective of this study was to establish the relationship between lignin content and the degradable fraction of warm-season grasses. The 120 samples used came from plots of the following species, Eragrostis curvula ev. Tanganyka (Ee), Panicum virgatum ev. Pathfinder (Pv), Panicum coIoratum ev. Selection 75 (Pe) and Tetrachne dregeí (Td). The samples were obtained during two consecutive winters, in 1990/91. The forage obtained was divided into its fractions, blade and stem+sheath, on which Iignin content (L) was determined. Each fraction was incubated within nylon bags, in the rumen of three fístulated steers. The Information obtained from incubations was mathematically processed to estimate the asymptote of the hyperbole (Dmax), and, through a non-linear model, the rapidly (a) and slowly (b) degradable dry malter values were determined. The contents of L were related to the values obtained by rumen incubation y, = (a+b) and Y2 = Dmax. Pseudovarlables were used to discriminate between grass species: Ee (Pv, Pe and Td=0); Pv (Pv = 1; Pe and Td=0); Pe (Pe = 1; Pv and Td=0);Td (Td=1; Pv and Pe=0). The equations obtained were, y, = 102.6 - 6.97L + 21.57Pv + 7.70Pe - 1.82L*Pe; R2 = 0.68(P
Keywords: Warm-season grasses; rumen degradability; Iignin; rumen